2022
DOI: 10.9734/ajaees/2022/v40i930988
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Attitude and Preference towards Crop Diversification with Maize in Haryana

Abstract: The study concluded that the scheme 'Mera Pani Meri Virasat' is proved helpful in crop diversification of paddy with maize. Farmers showed that armyworm in maize deteriorate the quality of maize which demotes the crop diversification from paddy with maize. The government’s assistance of Rs.7000/-per acre is less as compared to economic loss resulting from the attack of armyworms on maize. The farmers preferred the replacement of paddy with maize due to maize being fully mechanized as compared to paddy (partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…The results of the reliability statistics for the constructed attitude scale showed that the split half model reliability coefficient was 0.76, which indicated high internal consistency of the attitude scale constructed for the study. This is most crucial to attitude scale development as it shows the strength of the attitude scale [15].…”
Section: Reliability Testmentioning
confidence: 99%
“…The results of the reliability statistics for the constructed attitude scale showed that the split half model reliability coefficient was 0.76, which indicated high internal consistency of the attitude scale constructed for the study. This is most crucial to attitude scale development as it shows the strength of the attitude scale [15].…”
Section: Reliability Testmentioning
confidence: 99%